2017
DOI: 10.1093/ons/opx154
|View full text |Cite
|
Sign up to set email alerts
|

Middle Meningeal Artery Embolization as Treatment for Chronic Subdural Hematoma: A Case Series

Abstract: MMA embolization could present a minimally invasive and low-risk initial treatment alternative to surgery for symptomatic chronic SDH when clinically appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 10 publications
1
69
0
2
Order By: Relevance
“…The MMA has been in the center of interest of many studies regarding cephalalgia and migraine, due to the proposed vasodilatation‐based pathophysiological mechanisms, and hemodynamic studies (preferably noninvasive) are desperately needed . In the era of endovascular procedures, Doppler sonography of the MMA may be used to evaluate the outcomes of treatment of malformations and chronic subdural hematomas . MMA may contribute to the direct and indirect blood supply in chronic ischemic disease and Moya‐Moya, and exhibit increased flow velocities, with decreased RI …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MMA has been in the center of interest of many studies regarding cephalalgia and migraine, due to the proposed vasodilatation‐based pathophysiological mechanisms, and hemodynamic studies (preferably noninvasive) are desperately needed . In the era of endovascular procedures, Doppler sonography of the MMA may be used to evaluate the outcomes of treatment of malformations and chronic subdural hematomas . MMA may contribute to the direct and indirect blood supply in chronic ischemic disease and Moya‐Moya, and exhibit increased flow velocities, with decreased RI …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are no studies reporting visualizing the MMA or assessing its blood flow. Ultrasonographic visualization of the MXA and its MMA branch in ITF may allow their assessment in headache and migraine, intracranial hematomas, and extracranial‐intracranial by‐pass surgery, as well as to assess collateral flow development in carotid occlusive diseases and the vascularization of tumors and vascular malformations of the facial region …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature analysis by Tempaku et al of 21 patients who underwent MMA embolization as secondary therapy or concurrent therapy (in tandem with surgery) after attempts at surgical evacuation had failed found no incidence of recurrence . More recently, Link et al have reported on 5 patients who underwent embolization as primary therapy, also with promising results …”
mentioning
confidence: 99%
“…4 More recently, Link et al have reported on 5 patients who underwent embolization as primary therapy, also with promising results. 5 Although surgical evacuation remains the most common surgical option, this approach often requires prolonged time off of blood thinning medication. 3 There are only a few contraindications to endovascular embolization of the MMA, and if no anastomosis exists between external carotid artery ethmoidal branches and the ophthalmic artery it can be performed with minimal risk, under conscious sedation.…”
mentioning
confidence: 99%